Strengthening of autoclaved aerated concrete (AAC) masonry wallettes with fabric reinforced cementitious matrix for in-plane shear and out-of-plane loads. (May 2023) - Gupta, Akshay; Meena, Gaurav Kumar; Singhal, Vaibhav
Abstract: Autoclaved aerated concrete (AAC) masonry is popularly used for the construction of infill and partition walls in the RC and steel-framed structures. However, past research highlighted that AAC masonry may exhibit poor performance during seismic events due to its low tensile capacity. In this study, the flexural and shear performance of AAC masonry was enhanced by using the fabric-reinforced cementitious matrix (FRCM). This strengthening scheme was applied in two modes: direct mode using anchor and sandwich method using adhesive mortar. These strengthening schemes were different from each other in the method of placing of the fabric. The experimental results showed that the proposed strengthening methods could improve the strength and ductility of the masonry under shear and flexural loads. The test results showed comparable strengths for both types of strengthening methodologies and either of two methods of fabric application may be chosen for the strengthening of AAC masonry, depending on the availability of materials and ease in construction. Moreover, the outcome of the conducted tests were compared with the respective theoretical predictions estimated using available analytical models and equations.